2011
DOI: 10.4028/www.scientific.net/amr.261-263.807
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Influence of Polyacrylate Latex on Cement Mortars

Abstract: In this research, the physical and chemical influence of polyacrylate (PA) latex on cement-based materials were studied using polymer modified mortars with polymer/cement (P/C) ratios of 0%, 5% and 10%. Physically, the mechanical performance of PA latex modified mortars was investigated with compression toughness energy and bending strength. Further more, a comparison of the pore structure and porosity between PA latex modified and unmodified mortars was conducted. The chemical reactions between PA polymer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…PAE also has chemical reactions and physical behavior. They improve the performance of cement-based materials by connecting chemical bonds through chelation [ 76 , 77 ].…”
Section: Mechanism Of Acrylate-lotion-modified Cement-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAE also has chemical reactions and physical behavior. They improve the performance of cement-based materials by connecting chemical bonds through chelation [ 76 , 77 ].…”
Section: Mechanism Of Acrylate-lotion-modified Cement-based Materialsmentioning
confidence: 99%
“…Wang Ming et al [ 76 ] found three stages of chemical reactions in studying the mechanism of the PAE modification of cement-based materials. Ca(OH) 2 produced by the hydration of cement leads to the whole system being alkali-rich and exothermic in the first stage, which is very helpful to the hydrolysis of ester groups in the acrylate chain, causing the carboxyl group to be formed in the second stage.…”
Section: Mechanism Of Acrylate-lotion-modified Cement-based Materialsmentioning
confidence: 99%
“…The study showed that the addition of polyacrylamide could significantly prolong the setting time and improve its fluidity, among which the 3d and 28d flexural strengths increased by 75% and 39%, respectively, when the dosing amount was 0-0.3%, and the mechanical properties were greatly improved. In addition, polymers such as polyacrylic acid, polyurethane and epoxy [9][10][11] can improve the performance of sulfoaluminate cement very well. According to previous studies, it can be found that the macroscopic properties, such as the mechanics of polymer-reinforced cement matrix composites, are mainly studied, while the study of the interfacial interaction between the two phases at the nanoscale is still imperfect and challenging, occurring only through experimental studies, where molecular dynamics has a significant advantage [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, different chemical admixtures, for example, plasticisers, superplasticisers, viscosity-modifying agents, accelerators, anti-freezers, air-entrainers, volume stabilisers and numerous others, have been used extensively to adjust the properties of grouts as indicated by the worksite conditions and the aims of the grouting project [6][7][8][9][10][11][12][13][14]. Lately, there have been many types of water-soluble polymers and water-dispersed polymeric particles (latexes) being incorporated into mortars or concretes in order to improve their fluidity [15], mechanical properties [16], impact and abrasion resistance [17], waterproofness [18] and resistance to corrosive environments [19]. In particular, polymer-cement composites have demonstrated a discernible increase in mechanical strength because of the strong coherent matrix between the cement hydrate and the polymer membranes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%